Increasing lipid accumulation in Chlamydomonas by serial knocking out of DYRKP1 kinase and ADP-glucose pyrophosphorylase - Minjae Kim; Ji Yeon Kim; Kyong Ha Han; Hyeon Ho Shin; EonSeon Jin (Microbial Cell Factories)
Abstract Microalgae are promising sustainable feedstocks for biodiesel production. Among the primary carbon reservoirs in microalgae, starch and lipids are the main targets for metabolic engineering aimed at enhancing productivity. Redirecting carbon flux from starch toward lipid biosynthesis has been considered an effective strategy to improve lipid yield, and manipulating upstream regulators may allow broader control over metabolic networks. DYRKP1, a plant-specific dual-specificity tyrosine-phosphorylation-regulated kinase conserved in photosynthetic eukaryotes, has been implicated in regulating intracellular carbon partitioning. In this study, we investigated the physiological and metabolic effects of DYRKP1 deficiency in a cell-wall-less strain of Chlamydomonas reinhardtii. To further enhance lipid accumulation, we additionally knocked out ADP-glucose pyrophosphorylase (AGP), a key enzyme involved in starch biosynthesis. The total fatty acid content of DYRKP1-AGP double knockout (dKO) mutants was higher than that of their parental strain (CC4349) under both nitrogen-replete and deplete conditions, and was even 1.2-fold higher than that of the AGP single knockout (agp) mutant under nitrogen-deplete conditions. The DYRKP1 single knockout mutants exhibited fatty acid composition similar to the parental strain, regardless of nitrogen depletion. The fatty acid composition of the dKO mutants resembled that of the agp mutant under nitrogen-replete conditions, but diverged upon nitrogen starvation, suggesting a conditional interaction between upstream regulation and metabolic flux. This finding implies that disrupting upstream regulators like DYRKP1 may offer limited additional benefit when key downstream bottlenecks, such as starch biosynthesis, are already removed. Overall, our study underscores the layered complexity of carbon partitioning in C. reinhardtii and the importance of context-dependent metabolic regulation in optimizing lipid production.